Registration of Dahab Elgoz cowpea - Elawad, H.O.A.; Singh, B.B. (2003)
Dahab Elgoz'cowpea fVigna unguiculata (L.) Walp.] (Reg. no. CV-208, PI 632419. originally designated as 1T84S-2163) was developed by the International Institute of 'I'ropical Agriculture (ll'I'A) and distributed to various national programs in 1988 for testing and selection of suitable cultivars adapted to their own conditions. The cowpea researchers in Sudan tested this selection in two scparate sets of trials from 1988 to 1994 at the L,lobeid Research Station in the Sahelian zone of northwestern Sudan. It was also evaluated as a prereleased cultivar a1 three locations in North Kordofan. one location in West Kordofan. three locations in South Kordofan, and four locations in South Darfur across three seasons.'I'hese locations represent the environmental conditions o1 western Sudan and are where cowpea cultivation is predominant. On the basis of its continued superior performance, I1'84S-2163 was named Dahab Elgoz meaning Gold from the Sand and approvcd by the Agricultural Rescarch Corporation (ARC) and released by the National Variety Release Commitlee of Sudan lor general cultivation in June 2000.